BS EN IEC 61189-2-809. Test methods for electrical materials, printed board and other interconnection structures and assemblies. Part 2-809. X/Y Coefficient of Thermal Expansion Test (CTE) for Thick Base Materials by TMA (30th July 2021) - British Standards Institution,
No abstract available